Pichia pastoris as an expression host for membrane protein structural biology - Byrne,B (Current Opinion in Structural Biology, 2015)
The methylotrophic yeast Pichia pastoris is a widely used recombinant expression host. P. pastoris combines the advantages of ease of use, relatively rapid expression times and low cost with eukaryotic co-translational and post-translational processing systems and lipid composition. The suitability of P. pastoris for high density controlled culture in bioreactors means large amounts of protein can be obtained from small culture volumes. This review details the key features of P. pastoris, which have made it a particularly useful system for the production of membrane proteins, including receptors, channels and transporters, for structural studies. In addition, this review provides an overview of all the constructs and cell strains used to produce membrane proteins, which have yielded high resolution structures.